2022
DOI: 10.1159/000522560
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Neonatal Sequential Organ Failure Assessment and Mortality Risk in Preterm Infants with Necrotizing Enterocolitis

Abstract: <b><i>Introduction:</i></b> The neonatal sequential organ failure assessment (nSOFA) score is a tool for calculating mortality risk of infants in the neonatal intensive care unit. The utility of the nSOFA in determining the risk of mortality or the association with surgical intervention among infants with necrotizing enterocolitis (NEC) has not been investigated. <b><i>Methods:</i></b> We performed a retrospective, cohort study of preterm (&#x3c;37 weeks) inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 22 publications
1
24
1
1
Order By: Relevance
“…The neonatal SOFA (nSOFA) has been shown to predict the mortality of very preterm infants with late onset sepsis confirmed by blood culture findings [ 7 ]. In the recent large multicenter cohort of preterm patients with necrotizing enterocolitis (NEC), increased nSOFA scores predicted death or need for surgery [ 8 ]. Although other morbidities (early onset sepsis) may be more complex for organ dysfunction assessment, nSOFA can provide a standardized scoring algorithm related to mortality and/or morbidity in preterm infants [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…The neonatal SOFA (nSOFA) has been shown to predict the mortality of very preterm infants with late onset sepsis confirmed by blood culture findings [ 7 ]. In the recent large multicenter cohort of preterm patients with necrotizing enterocolitis (NEC), increased nSOFA scores predicted death or need for surgery [ 8 ]. Although other morbidities (early onset sepsis) may be more complex for organ dysfunction assessment, nSOFA can provide a standardized scoring algorithm related to mortality and/or morbidity in preterm infants [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Infection and in ammation has been identi ed as a risk factor for RDS [5] and Nupponen I et al showed that neutrophils were activated in neonates with RDS [6]. The nSOFA score is an operational de nition of organ dysfunction that can identify those preterm neonates with infection and sepsis and an increased risk of mortality [9,10], as sepsis is associated with a systemic in ammatory response which is implicated in the occurrence and development of RDS [6,20]. This study showed that the nSOFA score was strongly predictive of the mortality in neonates with RDS.…”
Section: Discussionmentioning
confidence: 99%
“…This study lled a gap in this eld, by determining the predictive power of the nSOFA score for mortality in RDS patients and its use to identify RDS patients at increased risk of adverse outcomes. As an objective measure of clinical course, nSOFA score has a potential utility both as a proxy variable for disease severity and as a risk assessment indicator for short-and long-term clinical endpoints [9]. In this study, the nSOFA score showed good correlation in most cases and its ndings will be useful for clinicians and researchers who need tools to objectively measure the risk of death, as well as for healthcare leaders and policy makers who develop resource allocation protocols for critically ill patients [24].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations